Data analysis in vegetation ecology - Wildi, Otto (Wiley-Blackwell, 2010)
Evolving from years of teaching experience by one of the top experts in vegetation ecology, Data Analysis in Vegetation Ecology aims to explain the background and basics of mathematical (mainly multivariate) analysis of vegetation data.